Evaluation of Arterial Erectile Dysfunction Using Shear Wave Elastography: A Feasibility Study. (14th September 2020) - Zhou, Wang; Zhang, Yuyang; Li, Liang; Gao, Jingjing; Zheng, Hui; Huang, Meng; Zhao, Sheng; Xie, Xinxin; Zhang, Chaoxue; Zhang, Xiansheng
Abstract : Objectives: To explore the feasibility of shear wave elastography (SWE) in the evaluation of arterial erectile dysfunction (ED). Methods: From November 2018 to November 2019, 26 patients with arterial ED and 30 patients with non‐vascular ED were prospectively included. SWE values of corpus cavernosum penis (CCP) and the flow velocity of cavernous artery for all patients in both before intracavernous injection (ICI) (flaccid state) and after ICI (erectile state) were measured. Performance of SWE value in assessing arterial ED was studied. Correlation between SWE value of CCP and the age of patients was also investigated. Results: ICI significantly reduced SWE values in both arterial and non‐vascular group (from 19.57 ± 6.33 KPa to 12.17 ± 3.64 KPa in the first, and from 19.91 ± 6.69 KPa to 8.04 ± 3.13 KPa in the former, both P < .001). SWE values of CCP after ICI in arterial ED were significantly larger than that in non‐vascular ED (P < .001). SWE values of CCP before ICI negatively correlated with age of patients in arterial ED (r = − 0.601, P < .001). With a cutoff value of 7.75 KPa, the area under curve, specificity, sensitivity, PPV, and NPV of SWE values of CCP after ICI in distinguishing arterial ED from non‐vascular ED were 0.810, 63.3%, 96.2%, 96.2%, and 70%, respectively. Conclusions: SWE was expected to be a potential technique for the noninvasive, simply operated, repeatable and quantitative evaluation of arterial ED. Abstract : Access the CME test here and search by article title.